Variables Related To The Formation Of Financial Statement Fraud With Beneish M Score In The Triangle Theory Concept Framework - Hani Fitria Rahmani; Lidya Oktalita (Jurnal AKSI (Akuntansi dan Sistem Informasi), 2023)
This research was conducted on manufacturing companies listed on the Indonesia Stock Exchange for the period 2018-2020. The purpose of this study was to determine how much influence Pressure, Opportunity, and Rationalization on Fraudulent Financial Statements were measured using the proxies of Financial Stability, Financial Target, External Pressure, Personal Financial Need, Ineffective Monitoring, Nature of Industry, and Rationalization. The unit of analysis in this study is the company's financial statements. The sample in this study as many as 23 companies during the research year period amounted to 3 years resulting in 69 respondents. The analytical method of this study uses logistic regression analysis. The conclusion of this study shows that Financial Stability and Ineffective Monitoring have an effect on Financial Statement Fraud. Meanwhile, Financial Target, External Pressure, Personal Financial Need, Nature of Industry, and Rationalization have no effect on Financial Statement Fraud